Hydrothermal Activity at a Cretaceous Seamount, Canary Archipelago, Caused by Rejuvenated Volcanism - Klügel, Andreas; Villinger, Heinrich; Römer, Miriam; Kaul, Norbert; Krastel, Sebastian; Lenz, Kai-Frederik; Wintersteller, Paul (Frontiers in Marine Science, 2020)
Our knowledge of venting at intraplate seamounts is limited. Almost nothing is known about past hydrothermal activity at seamounts, because indicators are soon blanketed by sediment. This study provides evidence for temporary hydrothermal circulation at Henry Seamount, a re-activated Cretaceous volcano near El Hierro island, close to the current locus of the Canary Island hotspot. In the summit area at around 3000-3200 m water depth, we found areas with dense coverage by shell fragments from vesicomyid clams, a few living chemosymbiotic bivalves, and evidence for sites of weak fluid venting. Our observations suggest pulses of hydrothermal activity since some thousands or tens of thousands years, which is now waning. We also recovered glassy heterolithologic tephra and dispersed basaltic rock fragments from the summit area. Their freshness suggests eruption during the Pleistocene to Holocene, implying minor rejuvenated volcanism at Henry Seamount probably related to the nearby Canary hotspot. Heat flow values determined on the surrounding seafloor (49 ± 7 mW/m2) are close to the expected background for conductively cooled 155 Ma old crust; the proximity to the hotspot did not result in elevated basal heat flow. A weak increase in heat flow towards the southwestern seamount flank likely reflects recent local fluid circulation. We propose that hydrothermal circulation at Henry Seamount was, and still is, driven by heat pulses from weak rejuvenated volcanic activity. Our results suggest that even single eruptions at submarine intraplate volcanoes may give rise to ephemeral hydrothermal systems and related marine ecosystems.